Wavelength dependent photoelectron circular dichroism of limonene studied by femtosecond multiphoton laser ionization and electron-ion coincidence imaging - Rafiee Fanood, Mohammad M.; Janssen, Maurice M. H.; Powis, Ivan (American Institute of Physics, 2016)
Enantiomers of the monoterpene limonene have been investigated by (2+1) resonance enhanced multiphoton ionization and photoelectron circular dichroism employing tuneable, circularly polarized femtosecond laser pulses. Electron imaging detection provides 3D momentum measurement while electron-ion coincidence detection can be used to mass-tag individual electrons. Additional filtering, by accepting only parent ion tagged electrons, can be then used to provide discrimination against higher energy dissociative ionization mechanisms where more than three photons are absorbed to better delineate the two photon resonant, one photon ionization pathway. The promotion of different vibrational levels and, tentatively, different electronic ion core configurations in the intermediate Rydberg states can be achieved with different laser excitation wavelengths (420 nm, 412 nm, and 392 nm), in turn producing different state distributions in the resulting cations. Strong chiral asymmetries in the lab frame photoelectron angular distributions are quantified, and a comparison made with a single photon (synchrotron radiation) measurement at an equivalent photon energy.